2011
DOI: 10.1158/1541-7786.mcr-10-0214
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Snail Is a Target Gene for HIF

Abstract: The transcriptional inhibitor Snail is a critical regulator for epithelial-mesenchymal transition (EMT). Although low oxygen induces Snail transcription, thereby stimulating EMT, a direct role of hypoxia-inducible factor (HIF) in this process remains to be demonstrated. Here we show that hypoxia induces the expression of Snail via HIF. In silico analysis identified a potential hypoxia-response element (HRE) close to the minimal promoter of the human and mouse genome of the snail gene. Gel shift assays demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 52 publications
3
78
0
1
Order By: Relevance
“…Furthermore, co-expression of any two or all markers correlated with a significantly worse prognosis, demonstrating the value of HIF-1α, Twist and Snail to predict the overall and recurrence-free survival in patients with resectable NSCLC. Although hypoxic induction of Snail transcription has been reported in multiple cancer types, an HRE in the minimal promoter of its gene SNAI1 has only recently been identified [74]. In addition to HIF-1α and HIF-2α binding to the HRE in its promoter region, expression of SNAI1 can be upregulated during hypoxia via other mechanisms, namely, Notch signaling.…”
Section: Inflammation Creates a Hypoxic Microenvironmentmentioning
confidence: 99%
“…Furthermore, co-expression of any two or all markers correlated with a significantly worse prognosis, demonstrating the value of HIF-1α, Twist and Snail to predict the overall and recurrence-free survival in patients with resectable NSCLC. Although hypoxic induction of Snail transcription has been reported in multiple cancer types, an HRE in the minimal promoter of its gene SNAI1 has only recently been identified [74]. In addition to HIF-1α and HIF-2α binding to the HRE in its promoter region, expression of SNAI1 can be upregulated during hypoxia via other mechanisms, namely, Notch signaling.…”
Section: Inflammation Creates a Hypoxic Microenvironmentmentioning
confidence: 99%
“…These authors further showed that the CDX2 promoter harbors a canonical E-box (CAGCTG, ~400 bp), which might serve as a binding site for Snail, but mutation of this site does not abolish repression by Snail (17). Therefore, our study focused on the expression of the transcriptional repressor Snail because Snail is a target gene for hypoxia (18). Our study showed that the expression of Snail mRNA was increased and achieved the peak at 24 h and remains elevated at 48 h in these two cell lines under mimicked hypoxic conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, hypoxia has also been implicated in up-regulating Snail expression because the Snail promoter had two potential HRE (Hypoxia-Response Elements) sites (18). Furthermore, hypoxia can act in synergy to control the up-regulated expression of Snail by augmenting Notch signaling in various tumor cell lines, including colorectal cancer (19).…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al, provided a strong evidence for the involvement of HIF-1α in inducing EMT by silencing HIF at 2% oxygen and over-expression of an oxygen-insensitive HIF mutant at 21% oxygen. Interestingly, expression of the oxygen-insensitive HIF mutant abrogated HIF mediated Snail activation and subsequent cell migration [21]. Their report identified Snail as a HIF target gene and provides novel insights into the regulation of Snail during hypoxia-induced EMT.…”
Section: Signaling Factors Involved In Epithelial-to-mesenchymal Tranmentioning
confidence: 94%